2012
DOI: 10.1352/1944-7558-117.3.207
|View full text |Cite
|
Sign up to set email alerts
|

Stress, Locus of Control, and Family Cohesion and Adaptability in Parents of Children with Down, Williams, Fragile X, and Prader-Willi Syndromes

Abstract: The present study analyzes differences in parental stress in families of children with Down, Williams, Fragile X, and Prader-Willi syndromes, exploring factors that influence parental stress, such as child's characteristics, parental locus of control, and family cohesion and adaptability. Differences between mothers and fathers are also investigated. Parents were given self-report questionnaires to assess family stress, parental locus of control, and family cohesion and adaptability. Results showed that stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
61
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(73 citation statements)
references
References 70 publications
9
61
1
2
Order By: Relevance
“…For example, child problem behaviors have consistently been suggested to play an important role in experienced strain (e.g., Baker et al, 2003; Neece, Green, & Baker, 2012; Osborne & Reed, 2009). Furthermore, research supports the notion that child factors may differentially contribute to levels of caregiver strain by diagnostic group (e.g., Abbeduto et al, 2004; Lanfranchi & Vianello, 2012). Child factors that have been explored extensively in this literature include adaptive and maladaptive behaviors, social/communication skills, and cognitive level (e.g., Baker et al, 2002, 2003; Davis & Carter, 2008; Neece & Baker, 2008; Weiss, Sullivan, & Diamond, 2003).…”
mentioning
confidence: 54%
See 2 more Smart Citations
“…For example, child problem behaviors have consistently been suggested to play an important role in experienced strain (e.g., Baker et al, 2003; Neece, Green, & Baker, 2012; Osborne & Reed, 2009). Furthermore, research supports the notion that child factors may differentially contribute to levels of caregiver strain by diagnostic group (e.g., Abbeduto et al, 2004; Lanfranchi & Vianello, 2012). Child factors that have been explored extensively in this literature include adaptive and maladaptive behaviors, social/communication skills, and cognitive level (e.g., Baker et al, 2002, 2003; Davis & Carter, 2008; Neece & Baker, 2008; Weiss, Sullivan, & Diamond, 2003).…”
mentioning
confidence: 54%
“…For example, Abbeduto et al (2004) found that parents of children with ASD had higher levels of strain when compared with parents of children with Down syndrome, but lower than those of children with Fragile X. When comparing caregivers of children with four different genetic disorders, Lanfranchi and Vianello (2012) found that parents of children with Down syndrome had significantly less strain than those of children with Prader-Willi syndrome. Furthermore, Schieve et al, (2007) emphasized that the differences in strain between caregivers of children with ASD and DD were washed-out with the inclusion of a variable capturing their recent need for specialized services.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…52,98 Based on a survey of 508 FXS families in 2011, one-third of mothers reported having seen a professional to treat depression, anxiety, or stress in the last year, and one-quarter reported taking prescription medication for these symptoms. 52,99 Stress is reported to be higher in families of children with FXS than those of children with Down syndrome, 100,101 which may be a result of increased child behavioral problems in FXS. 54, 102104 …”
Section: Resultsmentioning
confidence: 97%
“…Na adolescência e na idade adulta, esses indivíduos apresentam um novo dilema, encontrar um lugar na sociedade, um trabalho, buscar a satisfação da vida pessoal. E, nessa última fase, consequentemente, as famílias vivenciam experiências maiores de incerteza e estresse 11 . Estudos revelam que a escolaridade dos pais e as condições financeiras deles podem ter relação com a qualidade de vida 27,28 .…”
Section: Discussionunclassified